TRYBE®: an Fc-free antibody format with three monovalent targeting arms engineered for long in vivo half-life. Issue 1 (31st December 2023) - Davé, Emma; Durrant, Oliver; Dhami, Neha; Compson, Joanne; Broadbridge, Janice; Archer, Sophie; Maroof, Asher; Whale, Kevin; Menochet, Karelle; Bonnaillie, Pierre; Barry, Emily; Wild, Gavin; et al.
ABSTRACT: TrYbe® is an Fc-free therapeutic antibody format, capable of engaging up to three targets simultaneously, with long in vivo half-life conferred by albumin binding. This format is shown by small-angle X-ray scattering to be conformationally flexible with favorable 'reach' properties. We demonstrate the format's broad functionality by co-targeting of soluble and cell surface antigens. The benefit of monovalent target binding is illustrated by the lack of formation of large immune complexes when co-targeting multivalent antigens. TrYbes® are manufactured using standard mammalian cell culture and protein A affinity capture processes. TrYbes® have been formulated at high concentrations and have favorable drug-like properties, including stability, solubility, and low viscosity. The unique functionality and inherent developability of the TrYbe® makes it a promising multi-specific antibody fragment format for antibody therapy.